Marine navigation workbook piloting and celestial and electronic navigation - Hobbs, Richard R. (Naval Institute Press, 1998)
The standard navigation textbook at the U.S. Naval Academy and NROTC college programs for twenty-five years, this highly regarded reference has trained more than two generations of students on the practice of marine navigation in the U.S. Navy. All aspects of the duties, practices, and responsibilities of the Navy surface navigator at sea are covered. Long praised for its clarity and thoroughness, the text has now been revised and updated to reflect the latest changes in marine navigation technology and government publications.In this fourth edition all sight forms reflect those now in use in the U.S. fleet. Also included is new summary information on currently available computer navigation applications programs and new information on world geodesy and global positioning systems. Appendixes present the most important pages of Chart No. 1 and selected tables from the American Practical Navigator (Bowditch).Also available is the Marine Navigation Workbook, a chapter-by-chapter compendium of supplemental queries and problems designed to assist the student to master the material presented in the textbook -- complete with a handy three-ring binder. An appendix provides complete answers and solutions to all odd-numbered problems along with plotting sheets and forms. A new Instructor's Answer Key is available to bona fide instructors.